Tar Trap: No Evidence of Domestic Dog Burial with "La Brea Woman". (2nd January 2016) - Fuller, Benjamin T.; Southon, John R.; Fahrni, Simon M.; Harris, John M.; Farrell, Aisling B.; Takeuchi, Gary T.; Nehlich, Olaf; Richards, Michael P.; Guiry, Eric J.; Taylor, R. E.
Abstract : We radiocarbon dated the domestic dog found associated with La Brea Woman at the Rancho La Brea tar pits (Los Angeles, CA) to determine the validity of this human–dog connection. The domestic dog yielded a radiocarbon age of 3125 ± 25 14 C yr BP (3250–3400 cal yr BP) and La Brea Woman had a re-dated age of 9080 ± 15 14 C yr BP (10, 220–10, 250 cal yr BP). This ∼7000-year offset dispels the hypothesis this was an intentional and ceremonial human–dog burial.